Effects of Ultrafine Bubble Water on Gut Microbiota Composition and Health Markers in Rats - John Nicholas Jackowetz; Carly S. Hanson; Minto Michael; Kiriako Tsoukalas; Cassandra Villanueva; Peter A. Kozak (Nanomaterials)
Ultrafine bubbles (UFBs) represent an emerging technology with unique physicochemical properties. This study investigated the effects of air-filled UFBs infused in drinking water on gut microbiota composition and the associated health markers in Sprague Dawley rats over a 12-week period. Using a two-phase design, UFB concentration was increased from 1.7 × 106 to 6.5 × 109 UFBs/mL at week 7 to assess dose-dependent effects. Administration of UFBs in drinking water induced significant shifts in gut microbiome populations, characterized by increased Bacteroidetes (+122% weeks 8–12) and decreased Firmicutes (−43% weeks 8–12) compared to controls. These microbial shifts coincided with enhanced short-chain fatty acid production (butyrate +56.0%, p ≤ 0.001; valerate +63.1%, p ≤ 0.01) and reduced inflammatory markers (TNF-α −84.0%, p ≤ 0.05; IL-1β −41.0%, p ≤ 0.05; IL-10 −69.8%, p ≤ 0.05). UFB effects demonstrated systematic concentration-dependent threshold responses, with 85.7% of parameters exhibiting directional reversals between low (1.7 × 106 UFBs/mL) and high (6.5 × 109 UFBs/mL) concentration phases rather than linear dose–response relationships. The systematic nature of these threshold effects, with 71.4% of parameters achieving statistical significance (p ≤ 0.05), indicates concentration-dependent biological mechanisms rather than random effects on gut biology. Despite current metagenomic techniques identifying only 25% of the total gut microbiome, the observed changes in characterized species and metabolites demonstrate UFB technology’s therapeutic potential for conditions requiring microbiome modulation, providing new insights into UFB influence on complex biological systems.